2018
DOI: 10.1104/pp.18.00396
|View full text |Cite
|
Sign up to set email alerts
|

GLUCOSAMINE INOSITOLPHOSPHORYLCERAMIDE TRANSFERASE1 (GINT1) Is a GlcNAc-Containing Glycosylinositol Phosphorylceramide Glycosyltransferase

Abstract: Glycosylinositol phosphorylceramides (GIPCs), which have a ceramide core linked to a glycan headgroup of varying structures, are the major sphingolipids in the plant plasma membrane. Recently, we identified the major biosynthetic genes for GIPC glycosylation in Arabidopsis () and demonstrated that the glycan headgroup is essential for plant viability. However, the function of GIPCs and the significance of their structural variation are poorly understood. Here, we characterized the Arabidopsis glycosyltransfera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 45 publications
0
44
0
Order By: Relevance
“…Based on work performed in yeast where 3-ketosphinganine reductase suppressed Ca 2+ sensitivity (Beeler et al, 1998), the authors hypothesised that KDSR acts as a suppressor of the calcium signal during salt stress. Seeds of Atgint1 (glucosamine inositol phosphorylceramide trans-ferase1, responsible for the glycosylation of some GIPCs) mutants displayed a higher germination rate than WT in response to salt stress, although this difference disappeared at higher salt concentrations (Ishikawa et al, 2018). The Atacer mutant and AtACER RNAi lines displayed high ceramide levels but reduced LCBs due to a disruption of an alkaline ceramidase gene (Wu et al, 2015a).…”
Section: Salt Stressmentioning
confidence: 99%
“…Based on work performed in yeast where 3-ketosphinganine reductase suppressed Ca 2+ sensitivity (Beeler et al, 1998), the authors hypothesised that KDSR acts as a suppressor of the calcium signal during salt stress. Seeds of Atgint1 (glucosamine inositol phosphorylceramide trans-ferase1, responsible for the glycosylation of some GIPCs) mutants displayed a higher germination rate than WT in response to salt stress, although this difference disappeared at higher salt concentrations (Ishikawa et al, 2018). The Atacer mutant and AtACER RNAi lines displayed high ceramide levels but reduced LCBs due to a disruption of an alkaline ceramidase gene (Wu et al, 2015a).…”
Section: Salt Stressmentioning
confidence: 99%
“…Total sphingolipids were prepared from lyophilized rice tissues and quantified by LC-MS/MS as described previously [25,48]. The lipid content was represented as nmol per g dry weight (DW).…”
Section: Sphingolipidomic Analysismentioning
confidence: 99%
“…GIPCs, although one of the fundamental components of the plant PM model have been poorly studied, in part due to the absence of commercial preparations. Recent evidence has demonstrated that a loss of the glycosylation is lethal, (Ishikawa et al, 2018) (Rennie et al, 2014), and that misglycosylation affects both abiotic and biotic stress responses, as reviewed in (Mortimer & Scheller, 2020).…”
Section: Introductionmentioning
confidence: 99%